Lymphogranuloma venereum: the Italian experience. Issue 3 (26th November 2008) - Cusini, M; Boneschi, V; Arancio, L; Ramoni, S; Venegoni, L; Gaiani, F; de Vries, H J C
Abstract : An epidemic of lymphogranuloma venereum (LGV) has been described in men who have sex with men (MSM) in the western world, particularly in western Europe. The first Italian case was reported by the authors in 2006, and up to March 2008 there have been 13 symptomatic cases, all in MSM. Ten cases had LGV proctitis and three cases had inguinal adenopathy as their clinical presentation. The initial three cases reported receptive anal intercourse in metropolitan areas of northern Europe, Turkey and eastern Europe, whereas the later cases were infections acquired locally. Diagnosis was by LGV-specific real-time PCR in nine cases, by symptoms and PCR for Chlamydia trachomatis in three cases, and in one case clinically and epidemiologically.